PENYELESAIAN SENGKETA PAJAK: STUDI LITERATUR DAN REFORMASI PERPAJAKAN DI INDONESIA - Lukman Hakim Mustaqim, Aziz; Ihsan, Muhammad; Wahono, Puji; Pahala, Indra (Berajah Journal, 2024)
The purpose of this research is to examine the processes via which taxpayers and tax authorities in Indonesia resolve disputes over tax matters. A common source of conflict in the tax system is the ability of taxpayers to challenge judgments made by tax officials. This study employs a Systematic Literature Review (SLR) approach, which entails gathering and evaluating literature on tax dispute settlement. After determining which reputable journals are appropriate for SLR, the next steps are to assess and synthesise the results. Lack of accountability, effectiveness, and transparency in current processes is one of the key problems with tax dispute resolution, according to the report. The report concludes that changes to the tax system are necessary, and suggests implementing cooperative compliance principles to make the system more equitable and increase taxpayer happiness. Better and more equitable tax policy for Indonesia could be in the works thanks to this study's findings.